Global value chain assessment based on retrospectively induced economic costs associated with technology application: A case study of photovoltaic power system in Japan. (20th April 2018) - Tanaka, Kanako; Inoue, Toshihiro; Matsuhashi, Ryuji; Yamada, Koichi
Abstract: Global warming is a worldwide problem that requires an international strategy to ensure compatibility of economic growth and overcoming climate change. Although global use of low-carbon technology is a solution, consideration of economic consequences is important to promote future technology development and use. Photovoltaic (PV) solar power system is a promising renewable technology that carries climate mitigation expectations. We conducted a value chain analysis to evaluate the economic effect of the manufacture and use of silicon PV solar power system worldwide. We quantitatively reviewed the flow of manufacturing and installation for cells, modules, and facilities (e.g., inverters) related to Japan, and estimated the retrospectively induced economic costs for Japan and other developed and developing countries. Material, equipment, labor, utility, transportation, and business operation costs were studied in detail at different manufacturing and installation stages. This unique evaluation methodology quantified economic costs from an international perspective. The retrospectively induced economic effect of 2014 PV solar power system sales in Japan (induced by cell module and system production by Japanese companies and increased domestic use) was 1.6 trillion Japanese yen worldwide, of which 63% was attributable to Japan, 10% to other developed countries, and 27% to developing countries. The economic effect in Japan in terms of equipment cost and installation stage was 37% and 71% of the total effect, which was particularly high. Further technical improvement, cost reduction, and improvement in inverter and manufacturing equipment reliability are important to capitalize Japan's strengths. Currently, Japan's involvement in the manufacturing of cells and modules is small. Therefore, both technical innovation and cost reduction are necessary. We present new methodology to obtain inputs into policy development for further research, development, and technology diffusion. Graphical abstract: Image 1 Highlights: Evaluated retrospectively induced economic effect of the use of solar power system. The effect of 2014 PV in Japan was 1.6 trillion JPY worldwide. 63% was to Japan, 10% to other developed countries, and 27% to developing countries. The effect in Japan in terms of equipment cost and installation stage was high. A new method to obtain inputs into policy development for further R&D.